Effects of mangrove plantation on carbon and nitrogen stock accumulated in soil - Hong Hanh, Nguyen Thi; Tuan, Mai Sy (Academia Journal of Biology, 2014)
Mangrove forests absorb CO2 through the process of photosynthesis. The carbon is accumulated in trees, in litterfall and in soil. Estimation of carbon stock in mangrove soil helps evaluate the role of mangrove plantation in generating CO2- pools (green house gas) and serves as a means for valuation of carbon credits based on the Kyoto protocol approved in 2002 on Clean Development Mechanism applied to mangrove reforestation projects which enhanced the storage of carbon sink in nature. Thus, we have conducted a study on the effects of mangrove plantation on carbon and nitrogen stock accumulated in soil in Giaolac commune, Giaothuy district, Namdinh province. After a period of time of study (from December 2004 to December 2006), we have found that the mangrove plantations have affected the content of carbon and nitrogen accumulated in soil. The content of carbon and nitrogen in soil have changed with soil depths; the surface layer had the highest content of carbon and nitrogen in soil. The deeper soil layers, the less content of carbon and nitrogen. The litterfall production of the mangrove forests has affected the accumulation of carbon and nitrogen in forest soil. The accumulation of carbon and nitrogen below ground has occurred with time, tending to increase with the development of forest trees (1 year old forest: 69.337 ton carbon/ha; 8.667 ton nitrogen/ha; 9 year old forest: 108.043 ton carbon/ha; 12.984 ton nitrogen/ha). The bare area, where mangroves are not vegetated, has seen insignificant content of carbon and nitrogen accumulated in soil (50.766 ton carbon/ha; 4.231 ton nitrogen/ha). Mangrove forests have served as a carbon sink.